2009
DOI: 10.2166/wst.2009.472
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in a constructed wetland treating industrial wastewater: distribution in the sediment and rhizome tissue

Abstract: This study assessed copper and zinc distribution in the surface layer of sediment and rhizome tissue within the saturated surface vertical flow constructed wetland of CSBP Ltd, a fertiliser and chemical manufacturer located in Western Australia. Sediment and Schoenoplectus validus rhizome samples were collected at various distances from the inlet pipe while water samples are routinely collected. Water samples were analysed for nutrients and metals, sediments were analysed for total and bioavailable metals and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…However, previous research indicated that treatment wetland sediment can be significantly contaminated with metals, such as copper, zinc and cadmium (Domingo et al . ; Lesage et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…However, previous research indicated that treatment wetland sediment can be significantly contaminated with metals, such as copper, zinc and cadmium (Domingo et al . ; Lesage et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…The use of CW for the removal of Pb and Cr was under neutral and oxidizing conditions, which is a common finding in studies with similar operating conditions (Domingos et al 2009). Moreover, tolerance developed towards heavy metals occurs under the pH values registered the present study.…”
Section: Changes In Redox (E H ) and Phmentioning
confidence: 78%
“…Absence of significant differences between CWP I and CWP, is possibly related to the ability of emergent macrophytes to assimilate and distribute Cr and others heavy metals in their organs, this is independent of the microorganisms associated to their rhizosphere, as suggested by studies on phytoremediation (Eapen and D'Souza 2005;Domingos et al 2009). …”
Section: Fate Of Pb and Cr In Cw Containing Metal-tolerant Bacteriamentioning
confidence: 95%
See 1 more Smart Citation
“…With a total holding volume of 7695m 3 , an average theoretical hydraulic retention time (HRT) of 6.9 days can be assumed. Heavy metal removal performance for this wetland has been described by Domingos et al (2009). …”
Section: Wastewater and Wetland Descriptionmentioning
confidence: 99%